Relationship between interprofessional collaboration and psychological distress experienced by healthcare professionals during COVID-19: a monocentric cross-sectional study - Ruttmann, Kirstin; Albaladejo-Fuertes, Sheila; Lindenberg, Nicole; Kunst, Claudia; Mehrl, Alexander; Kindl, Vera; Gülow, Karsten; Schlosser-Hupf, Sophie; Schmid, Stephan; Müller, Martina (Frontiers in Medicine, 2024)
Background Since the onset of the COVID-19 pandemic, global healthcare systems have faced unprecedented challenges, leading to significant psychological distress among healthcare professionals. Recognizing the importance of enhanced interprofessional collaboration in alleviating this burden, as emphasized by the World Health Organization in 2020, we investigated whether such collaboration could mitigate staff psychological distress during crises. To our knowledge, no study has yet explored the role of interprofessional collaboration as a resilience factor in crises. Methods For this monocentric cross-sectional study at a German university hospital, we examined the relationship between the quality of interprofessional collaboration and the psychological distress of healthcare professionals during the initial pandemic wave. We employed validated mental health instruments, such as the GAD-7 and PHQ-2, to assess anxiety and depressive symptoms. Additionally, custom-designed questionnaires evaluated “Pandemic-Associated Burden and Anxiety (PAB; PAA)” and interprofessional crisis management experiences. A novel “Interprofessional collaboration and communication (IPC)” assessment tool was developed based on international competency frameworks, demonstrating strong reliability. Results The study involved 299 healthcare professionals (78.6% in direct contact with COVID-19 patients). Moderate levels of PAB/PAA were reported. However, a significant proportion experienced clinically relevant anxiety, as indicated by GAD-7. Negative IPC perceptions correlated with higher levels of psychological distress. Linear regression analysis showed associations between interprofessional collaboration and anxious and depressive symptoms, and pandemic-related burden. Conclusion Our findings highlight the vital role of enhanced interprofessional collaboration in strengthening the psychological well-being of healthcare professionals during crises. The study underscores the need to foster a collaborative environment and integrate interprofessional education for resilience.